Minimizing bleeding risks during gastric neuroendocrine tumor endoscopic submucosal dissection by pre-emptive EUS-guided epinephrine injection - Radhika Chavan, MD, DNB, FISG, FASGE; Vishal Seth, MD, DM; Zaheer Nabi, MD, DNB, FISG, FASGE; Dadasaheb Maindad, MD, DNB; Harshwardhan Dongre, DNB; Sanjay Rajput, MD, DM; Akhil Nagpal, MD, DM (VideoGIE)
Background and Aims: Gastric neuroendocrine tumors (NETs), although rare, are highly vascular subepithelial lesions that can pose significant bleeding risks during endoscopic submucosal dissection (ESD). Traditionally, bleeding is managed intraoperatively with mechanical or thermal hemostasis, but pre-emptive strategies remain underexplored. Here, we report the use of EUS-guided pre-emptive epinephrine injection to minimize the bleeding risk during gastric NET ESD. Methods: To minimize the risk of bleeding during ESD of large gastric NETs, a pre-emptive EUS-guided epinephrine injection was administered at the base of the lesion near the feeder vessel. Results: A 38-year-old female was diagnosed with a large gastric subepithelial lesion during evaluation for upper gastrointestinal bleeding. EUS revealed a large hypoechoic tumor confined to the submucosa with a prominent feeding vessel. Given the predominantly submucosal location, ESD was planned. However, significant bleeding was anticipated due to the large feeder vessel. Therefore, a pre-emptive EUS-guided adrenaline injection (5 mL of 1:10,000 diluted epinephrine) was administered at the base of the lesion after confirming absence of blood return on fine-needle aspiration. Instantaneous pallor of the lesion was observed. ESD was subsequently completed successfully without any bleeding. Conclusions: This case highlights a novel, effective, and safe use of EUS-guided pre-emptive epinephrine injection to minimize bleeding during ESD of vascular gastric NETs. This approach could enhance procedural safety and warrants further prospective evaluation.